South Africa's role in the Civil War in Russia 1918-1920 - Bisset, W.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
South Africa's role in the Civil War in Russia (1917 -1920) has never been fully researched and it is probable that relatively few people are aware that South Africans were among those who fought against the Red Army in 1918-1920. Although it has not been possible to trace a roll of members of the South African Forces who served in Russia between 1918 and 1920, their autobiographies and letters published in The Nongqai have made it possible to compile an interim report on the subject. However, it is important to note that even if the roll of members of the South African Forces who served in Russia could be traced or compiled from the personnel record cards in the SADF Archives, this would not provide a complete picture because a number of the South Africans who served in Russia had served in the British Forces throughout the Great War.